Pengaruh Penggunaan Media Pembelajaran TIK terhadap Hasil Belajar Tematik Kelas IV SDN KIP Maccini - Nurhayati Selvi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The current learning follows the pandemic situation that hit Indonesia. Any activity is required to follow the health protocol. The purpose of this study is to maximize the implementation of learning by using information and communication technology media in learning and to find the effect of using information and communication technology learning media on learning outcomes. Quantitative research approach, the type of experiment with a quasi-experimental design. This research is located at SDN KIP Maccini with a population of fourth grade students for the 2020/2021 academic year. The sampling technique used purposive sampling, so the sample was 20 students. Data collection techniques: tests, observations and documentation. Analysis technique: Descriptive and inferential statistics, hypothesis test dependent T-Test. The results showed that the use of information and communication technology media in fourth grade students of SDN KIP Maccini, its implementation using information and communication technology media could be said to be well implemented. This can be seen from the activeness of students during the learning process and the implementation of aspects observed through teacher and student observations. The use of information and communication technology media affects the learning outcomes of SDN KIP Maccini.